The Current State of Private Security and Municipal Police in the Slovak Republic - Andrej, Veľas; Zuzana, Zvaková (Magyar Rendészet, 2025)
The article contains a short description of the history of private security services and municipal police in the Slovak Republic. At the same time, it contains the position and tasks of both these security forces in the protection of persons and property, competences of private security services and municipal police, specifics, shortcomings and opportunities for their further development. More than 30 years of independence of the Slovak Republic have brought specifics that place the Slovak and Czech Republics as former common Czechoslovakia in different planes. Private security services are an inseparable part of the protection of private property and municipal police of public property. Private security services are characterised by the national minimum wage and often unprofessional interventions, which is due to the pressure of state institutions and enterprises to reduce prices in the procurement of these services. Unlike private security services, municipal police forces are well trained and equipped. Salary conditions and retirement pensions are also an attraction for young people. The two security forces are part of a rather large system and are incomparable, so they will be described separately in two sections.